Microstructural Design and Processing Control of Advanced Ceramics - Wang, Qingyuan; Chen, Yu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advanced ceramics are referred to in various parts of the world as technical ceramics, high-tech ceramics, and high-performance ceramics. Advanced ceramics have better performances in quality as well as new applications that traditional ones do not have. They have multiple physical and mechanical properties including high hardness, high strength, thermal shock resistance, wear resistance, corrosion resistance, and high-temperature resistance. In view of these characteristics, advanced ceramics are often high value-added products. Developments in advanced ceramics continue at a rapid pace, constituting what can be considered a revolution in the kind of materials and properties obtained.This reprint is intended for material researchers and application developers who seek information on the microstructural design and processing control of advanced ceramics, including piezoelectric ceramics, high-temperature ceramic composites, ceramic coatings, metal glasses, etc.